PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SD NEGERI 196 POLEWALI KABUPATEN SOPPENG - A. Nurul Aliyah, Waode.; Nurfaizah AP, Andi; Abidah Idrus, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning motivation of students in Pancasila Education, as indicated by the lack of enthusiasm, participation, and cooperation during the learning process. The purpose of this study was to improve students’ learning motivation through the implementation of the Cooperative Learning Model Type Make A Match. This model was designed to create an active and enjoyable learning atmosphere while encouraging students to collaborate through a card-matching activity consisting of questions and answers. This study employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were fifth-grade students of SD Negeri 196 Polewali, Soppeng Regency. Data were collected through teacher activity observation sheets and student learning motivation questionnaires. The data were analyzed qualitatively and quantitatively to determine the improvement in teacher performance and student learning motivation after applying the Make A Match model.The results showed that implementing the Make A Match learning model increased students’ learning motivation. Teacher activity improved from the “fair” category to “good,” while students became more active, enthusiastic, and engaged in the learning process.In conclusion, the Cooperative Learning Model Type Make A Match was effective in improving students’ learning motivation in Pancasila Education at Grade V of SD Negeri 196 Polewali, Soppeng Regency.